Hydrophobic Shielding of Outer Surface: Enhancing the Chemical Stability of Metal–Organic Polyhedra. Issue 4 (2nd January 2019) - Mollick, Samraj; Mukherjee, Soumya; Kim, Dongwook; Qiao, Zhiwei; Desai, Aamod V.; Saha, Rajat; More, Yogeshwar D.; Jiang, Jianwen; Lah, Myoung Soo; Ghosh, Sujit K.
Abstract: Metal–organic polyhedra (MOP) are a promising class of crystalline porous materials with multifarious potential applications. Although MOPs and metal–organic frameworks (MOFs) have similar potential in terms of their intrinsic porosities and physicochemical properties, the exploitation of carboxylate MOPs is still rudimentary because of the lack of systematic development addressing their chemical stability. Herein we describe the fabrication of chemically robust carboxylate MOPs via outer‐surface functionalization as an a priori methodology, to stabilize those MOPs system where metal–ligand bond is not so strong. Fine‐tuning of hydrophobic shielding is key to attaining chemical inertness with retention of the framework integrity over a wide range of pH values, in strong acidic conditions, and in oxidizing and reducing media. These results are further corroborated by molecular modelling studies. Owing to the unprecedented transition from instability to a chemically ultra‐stable regime using a rapid ambient‐temperature gram‐scale synthesis (within seconds), a prototype strategy towards chemically stable MOPs is reported. Abstract : Systematic stability : A correlation between the hydrophobicity and chemical stability of metal–organic polyhedra (MOP) was uncovered. Enhancement of the chemical stability is a consequence of the incremental hydrophobicity of the surfaces for systems where the internal core of each cage is similar. Structural characterizations and simulation data are presented.